2010
DOI: 10.1097/ta.0b013e3181958b66
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorders are Not Associated With Nonrecovery in Patients With Traffic-Related Minor Musculoskeletal Injuries

Abstract: PDs are common among patients with minor traffic-related musculoskeletal injuries. Our study does not support the view that PDs are associated with nonrecovery. The patient's mental health status at the time of the crash seems to be more important for nonrecovery than a PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Even though minor injuries comprise approximately 75% of all road transport injuries, poor physical and mental health outcomes in this group have received little attention . Among participants with minor injuries, there are individuals at high risk of substantial poor recovery and on‐going disability . Hence, permanent or temporary disabilities arising from minor injuries pose an on‐going problem for the compensation and health‐care system .…”
Section: Introductionmentioning
confidence: 99%
“…Even though minor injuries comprise approximately 75% of all road transport injuries, poor physical and mental health outcomes in this group have received little attention . Among participants with minor injuries, there are individuals at high risk of substantial poor recovery and on‐going disability . Hence, permanent or temporary disabilities arising from minor injuries pose an on‐going problem for the compensation and health‐care system .…”
Section: Introductionmentioning
confidence: 99%
“…It must be pointed out, however, that knowledge concerning prevalence rates of PDs in general trauma populations is scarce, although it is known that extreme expression of some personality traits as such is related to risk behavior [50,51]. In one study, an increased prevalence of PDs in a traffic-related trauma population was identified [52]. Participants meeting criteria for a PD diagnosis reported lower scores than those without a PD diagnosis in only one aspect of burn-specific health, the BSHS-B domain skin involvement.…”
Section: Discussionmentioning
confidence: 95%
“…The participants studied in the frame of this thesis originate from four different cohorts (Figure 8). Cohort (135 individuals) is derived from a larger material, which has been the source of several published studies [42,[103][104][105]. The original RCT [103] consisted of patients with various musculoskeletal injuries secondary to MVA who were admitted to the emergency department.…”
Section: Methodsmentioning
confidence: 99%